Compara????o das respostas cardiopulmonares entre o shuttle walk test incremental e teste ergoespirom??trico em esteira em pacientes hemipar??ticos decorrente de AVC - Sousa, Maria Helena Gomes de (2018)
Ergospirometric test, gold standard evaluation of cardiorespiratory fitness, is not an economically accessible and easy to apply test, especially for patients with Cerebral Vascular Accident (CVA) sequelae. Thus, field tests such as the Shuttle Walk Test Incremental (SWTI) may be another option for evaluation of cardiorespiratory function. Objective: compare the ventilatory, metabolic and cardiovascular responses obtained by the SWT and ergospirometric test, in hemiparetics due to stroke. Secondary objective was compared with the results of the ventilation evaluations with mild, moderate, marked and severe motor impairment of hemiparetic patients. Methodology: transversal study, with 20 hemiparetic subjects, motor impairment (05 mild, 04 moderate, 05 severe, 06 severe), 58 ?? 10 years old, 08 women and 12 men. The VO2maximum (VO2), ventilatory (VE), desaturation, heart rate (HR) and blood pressure (BP), during the SWTI and ergospirometry, were evaluated in two days, 48h interval. Results: SpO2 was similar (97 [96-98]; 97 [94-97]) respectively in SWT and ergospirometry. VO2Pico metabolic variables (18 ?? 4, 24 ?? 4), cardiac FCPic (101 ?? 17, 115 ?? 15), systolic BP (140 [140-147], 160 [140-160]) and diastolic (2 ?? 1, 3 ?? 1), fatigue (2 [1-4], 4 [2-6]) and distance traveled (248 ?? 154, 409 ?? 1) 216). Comparison between groups of motor severity: ergospirometry showed variance in VO2peak and distance traveled between the light and severe group (p <0.05); others did not show significant differences. No SWTI, VO2Pico presented the difference between the moderate and striking groups (p <0.05) and the distance traveled between the light, striking and severe groups (p <0.05). Conclusion: SWTI is not similar to ergospirometry in the hemiparetic population due to stroke. Severe patients have poorer performance in both tests compared to the mild and moderate group, according to a Fugl-Meyer scale.